2007
DOI: 10.1091/mbc.e07-01-0047
|View full text |Cite
|
Sign up to set email alerts
|

Dystroglycan and ProteinO-Mannosyltransferases 1 and 2 Are Required to Maintain Integrity ofDrosophilaLarval Muscles

Abstract: In vertebrates, mutations in Protein O-mannosyltransferase1 (POMT1) or POMT2 are associated with muscular dystrophy due to a requirement for O-linked mannose glycans on the Dystroglycan (Dg) protein. In this study we examine larval body wall muscles of Drosophila mutant for Dg, or RNA interference knockdown for Dg and find defects in muscle attachment, altered muscle contraction, and a change in muscle membrane resistance. To determine if POMTs are required for Dg function in Drosophila, we examine larvae muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 44 publications
(81 reference statements)
2
62
1
1
Order By: Relevance
“…1D) (Desai et al, 1994;Beumer et al, 2002). Similarly, Dystroglycan (DG) is reportedly the primary substrate for VVA labeling at the NMJ (Haines et al, 2007;Nakamura et al, 2010). Both HRP and VVA labeling are absent at Mgat1 null NMJs (Fig.…”
Section: Mgat1 Shapes the Glycosylated Synaptomatrix Of The Nmjmentioning
confidence: 82%
See 1 more Smart Citation
“…1D) (Desai et al, 1994;Beumer et al, 2002). Similarly, Dystroglycan (DG) is reportedly the primary substrate for VVA labeling at the NMJ (Haines et al, 2007;Nakamura et al, 2010). Both HRP and VVA labeling are absent at Mgat1 null NMJs (Fig.…”
Section: Mgat1 Shapes the Glycosylated Synaptomatrix Of The Nmjmentioning
confidence: 82%
“…For example, the widely employed anti-HRP antibody binds fucosylated N-glycans in the presynaptic membrane, which require Mgat1 for fucose modification (Sarkar et al, 2006). Likewise, VVA lectin is a synaptic glycan marker at the Drosophila NMJ, which reportedly recognizes primarily postsynaptic Dystroglycan (Haines et al, 2007;Rushton et al, 2012). The endogenous MTG lectin patterns the extracellular glycosylated synaptomatrix (Rohrbough et al, 2007), modulates trans-synaptic signaling and is essential for functional synaptogenesis (Rushton et al, 2009;Rohrbough and Broadie, 2010).…”
Section: Mgat1 Shapes the Glycosylated Synaptomatrix Of The Nmjmentioning
confidence: 99%
“…In Drosophila, Dg has been reported to play a fundamental role for polarizing the epithelial cells and the oocytes in the ovaries (Deng et al, 2003). In larval body wall muscles, errors in muscle attachment, muscle contraction, and muscle membrane resistance have been associated with Dg mutant alleles and RNAi mediated reduction of Dg (Haines et al, 2007). Originally, Dg was isolated from skeletal muscle membranes and was found to be an essential component of the dystrophin-glycoprotein complex, which links the ECM surrounding myofibers to the actin cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…O-Mannosylation is essential for maintaining cell shape and cell integrity (21) and contributes to quality control of proteins in the endoplasmic reticulum (ER) in yeast (22,23). Reduction of protein O-mannosyltransferases in Drosophila melanogaster resulted in defects in embryonic muscle development (24)(25)(26)(27) and pomt1 deletion in mouse resulted in embryonic death (28). Recently, we also demonstrated that O-mannosyltranserase was required for muscle development in zebrafish (29).…”
Section: B O-mannosyltransferase (Pomt)mentioning
confidence: 99%